Clinical and Patient‐Reported Outcomes of Single Posterior Implant‐Supported Restorations Completed by Predoctoral Students: A Retrospective Study with Up to 10 Years of Follow Up. Issue 2 (11th December 2020) - Bompolaki, Despoina; Edmondson, Sara A.; Katancik, James A.; Kamposiora, Phophi; Papavasiliou, George
Abstract: Purpose: To assess clinical outcomes of screw‐retained implant‐supported restorations as well as patient satisfaction and Oral Health‐related Quality of Life (OHQoL), when treatment is performed in an academic setting by supervised predoctoral students. Materials and methods: Ninety patients (n = 129 restorations) consented to participate in the study. The mean follow‐up period was 4.2 years (range: 4 months to 10.6 years) after crown insertion. All patients filled out a modified Oral Health Impact Profile questionnaire, consisting of 14 questions (OHIP‐14). A comprehensive examination of the implant‐supported restoration was completed and restorative complications were recorded. Statistical analysis was performed using SPSS (IBM SPSS Statistics, v25; IBM Corp). Restoration survival rates were calculated using Kaplan‐Meier survival analysis. Results: The most frequent complication was loss of the mesial interproximal contact (32.2%). The overall restoration survival and success rates were 93.8% and 74.4%, respectively. The majority of patients (95.6%) reported high satisfaction with their decision to get implant treatment in the predoctoral clinic. Conclusions: In the context of this study, clinical and patient‐based outcomes of implant treatment rendered in an academic setting are favorable and comparable to those reported in the literature for restorations completed by experienced dentists.